Association of Preablation Plasma Corin Levels With Atrial Fibrillation Recurrence After Catheter Ablation: A Prospective Observational Study - Yichang Zhao; Xiaoyang Yuan; Yunpeng Xie; Xiaomeng Yin; Ying Liu; Yuanjun Sun; Yue Gong; Jinqiu Liu; Feifei Chen (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2024)
Background We assessed the impact of pre‐ and postprocedural plasma corin levels on the recurrence of atrial fibrillation (AF) after catheter ablation (CA). Methods and Results This prospective, single‐center, observational study included patients undergoing their first CA of AF. Corin was measured before and 1 day after CA. The primary end point was recurrent AF between 3 and 12 months after ablation. From April 2019 through May 2021, we analyzed 616 patients with AF (59.09% men) with a mean age of 62.86±9.42 years. Overall, 153 patients (24.84%) experienced recurrent AF. In the recurrence group, the pre‐ and postprocedure corin concentrations were 539.14 (329.24–702.08) and 607.37 (364.50–753.80) pg/mL, respectively, which were significantly higher than the nonrecurrence group's respective concentrations of 369.05 (186.36–489.28) and 489.12 (315.66–629.05) pg/mL (both P<0.0001). A multivariate Cox regression analysis with confounders found that elevated preablation corin levels were significantly associated with an increased risk of AF recurrence after CA. Receiver operating characteristic curve analysis identified that a preablation corin threshold of >494.85 pg/mL predicted AF recurrence at 1 year. An increase of 1 SD in corin concentrations before CA (264.94 pg/mL) increased the risk of recurrent AF by 54.3% after adjusting for confounding variables (hazard ratio, 1.465 [95% CI, 1.282–1.655]; P<0.0001). Conclusions Plasma corin levels at baseline is a valuable predictor of AF recurrence after CA, independent of established conventional risk factors. Risk stratification before ablation for AF may be useful in selecting treatment regimens for patients.